PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERBASIS CTL DENGAN METODE MAKE A MATCH UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA KELAS VIII (UPEJ Unnes Physics Education Journal, 2012)
This research is used to determine whether there are differences in increasedunderstanding of physics concepts after CTL-based model of cooperativelearning to make a match method was applied to class VIII. The method usedwas nonequivalent control group design. Based on gain test found thatincreasing the concepts of physics in the experimental group is higher thanthe control group. It can also be known in the different average test. Thesignificant different is all shown true with ttest with tcount = 2.597 in ttable =1.994. These results are also suported by the observation that the test resultsfor the experimental group reached a value of 63.19 with is in quite wellcategory but the control group only reached a value of 54.86 with is in unfavorable category. This study was not able to reach minimum terms ofclassical completeness. The experimental group achieved 63.89% while thecontrol group achieved 33.33%. This is because the strategy may only besuitable for some students and the discussion can not be predicted. However,overall it can be concluded that the CTL-based cooperative learning model tomake a match method can improve the understanding of the physics conceptof class VIII.